Experimenting with Sensorimotor Play to Enhance Learning Attention and Cognitive Function in Children at TK SPNF SKB Denpasar - Ratini, Ni Kadek; Narta Dewi, Anak Ayu Nyoman Trisna; Nugraha, Made Hendra Satria; Utama, Anak Agung Gede Eka Septian (Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction: Children need attention and education from their families, schools, and communities to support their development. Cognitive function, especially attention, is vital for their learning process. Previous studies have shown suboptimal cognitive function (average digit span test score of 4.31) and decreased attention during lessons, evidenced by frequent seat changes and talking. Enhancing these areas through sensorimotor play can create more engaging and enjoyable learning experiences for children. Methods: This quasi-experimental study utilized consecutive sampling to determine a sample size of 30 children based on Pocock's formula. Two classes from TK SPNF SKB were randomly selected, and subjects were assessed for eligibility based on inclusion and exclusion criteria. The subjects were randomly divided into 15 children in the intervention group and 15 in the control group. The intervention group participated in sensorimotor play sessions three times a week for three weeks, totaling nine sessions, each lasting 30-35 minutes. The control group did not receive any intervention. Results: Data analysis using paired sample t-tests demonstrated a significant improvement in the intervention group's learning attention (p = 0.001) and cognitive function (p = 0.001). Independent t-test results indicated an essential difference between the two groups post-intervention (p = 0.001). Conclusion: Sensorimotor play effectively enhances attention and cognitive function in children. Keywords: sensorimotor play, learning attention, cognitive function